Computerised parts traceability an implementation case study - Sohal, Amrik S.
In order to assess product quality it was deemed necessary to have an effective computerised system for parts traceability. Its value has been demonstrated in a case study of a large automotive parts manufacturer.
This case study examines the planning and implementation of a computerised parts traceability system at Nippondenso (Australia), a large automotive parts manufacturer located in Melbourne, Australia. The paper discusses the associated planning and training, hardware and software selection, implementation problems and benefits achieved from the implementation. Factors critical to successful implementation are also identified. In early 1990 the Australian car manufacturers demanded that Nippondenso fully identify and trace every component to assure product quality. A five-year plan for computer integrated manufacture (CIM) was developed by Nippondenso (Australia), with an initial emphasis on gaining full traceability of products. The computerised system put in place enables the identification of all incoming goods, direct requisition of those goods from computer terminals at the shop floor and recording of all work and processes used in manufacture. The manufacturing history of every finished product is then stored and is both precise and complete. In addition to a higher level of quality assurance through traceability of faulty parts, Nippondenso (Australia) has gained significant savings from better stock handling and production management. Accurate information regarding work-in-progress and inventory levels greatly aids decision making and has reduced lead times.
Keywords: Computerised parts traceability